The Effect of Trophic Modes on Biomass and Lipid Production of Five Microalgal Strains - Nicodemou, Andonia; Kallis, Michalis; Agapiou, Anastasia; Markidou, Androulla; Koutinas, Michalis (My University, 2022)
Five microalgae strains, namely Isochrysis galbana, Microchloropsis gaditana, Scenedesmus obliquus, Nannochloropsis oculata and Tetraselmis suecica, were selected as potential candidates for polyunsaturated fatty acids’ production, evaluating biomass productivity and their capacity to accumulate high lipid contents under different trophic modes. Microalgae strains were cultivated in the presence of 1% glucose using mixotrophic and heterotrophic conditions, while autotrophic cultures served as control experiments. The results demonstrate that S. obliquus performed the highest biomass productivity that reached 0.13 and 0.14 g L−1 d−1 under mixotrophic and heterotrophic conditions, respectively. I. galbana and S. obliquus utilized elevated contents of glucose in mixotrophy, removing 55.9% and 95.6% of the initial concentration of the carbohydrate, respectively, while glucose consumption by the aforementioned strains also remained high under heterotrophic cultivation. The production of lipids was maximal for I. galbana in mixotrophy and S. obliquus in heterotrophy, performing lipid productivities of 24.85 and 22.77 mg L−1 d−1, respectively. The most abundant saturated acid detected for all microalgae strains evaluated was palmitic acid (C16:0), while oleic and linolenic acids (C18:1n9c/C18:3n3) comprised the most abundant unsaturated fatty acids. I. galbana performed the highest linoleic acid (C18:2n6c) content under heterotrophic nutrition, which reached 87.9 mg g−1 of ash-free dry weight. Among the microalgae strains compared, the biomass and lipid production monitored for I. galbana and S. obliquus confirm that both strains could serve as efficient bioproducers for application in algal biorefineries.
Keywords: Polyunsaturated fatty acids; Microalgae; Mixotrophic; Heterotrophic; Lipid accumulation; Biomass